MERENUNGKAN KEMBALI PROFESI GURU - Ayu Nindya Wahono; Tasya Ratri Putri; Ririn Susanti Maghdalena (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2023)
Education is closely related to various resources in it, including teachers. 2022 is the year of building the foundation of education by incorporating elements of technology in it. With the theme